Cultivation techniques of grafted watermelon, effects on yield and fruit quality - Orrala Borbor, Nèstor Alberto; Herrera Isla, Lidcay Felipe; Balmaseda Espinosa, Carlos Eloy (Revista Mexicana de Ciencias Agrícolas, 2019)
In order to investigate the effect of rootstock patterns and cultivation techniques on the yield and quality of watermelon fruit, a study was conducted between October 2014 and February 2015 in the municipality of Santa Elena, Ecuador. The watermelon hybrid Royal Charleston grafted on three patterns (Shintoza, RS-841, Ercole interspecific hybrids of Cucurbita maxima x Cucurbita moschata), three planting densities (3 000, 3 500, 4 000 plants ha-1), pruning were evaluated (without pruning, three and four main guidelines) and three doses of gibberellic acid (0, 10, 20 mg L-1), applied in the transplant and 20 and 40 days after it, in an orthogonal design L9 (3)4 arranged in random blocks with three replicas. The variables evaluated were stem diameter, fruits per plant, fruit mass, agricultural yield (t ha-1), total soluble solids, pulp firmness and bark thickness. In addition, the ‘regular analysis’ was carried out, which includes the preparation of the response table, selection of the optimal combination and the prediction of the maximum response. The Royal Charleston watermelon hybrid grafted onto the RS-841 pumpkin pattern, using the approximation method, with a density of 4 000 plants ha-1, four main guides and the application of 20 mg L-1 gibberellic acid respectively, reached the greater amount of fruits per plant and therefore higher yield, result that was confirmed by the regular analysis performed.
Keywords: Citrullus lanatus; density; grafting; production; pruning